2019
DOI: 10.3390/ijms20246107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of B Cell Epitopes of Blo t 13 Allergen and Cross-Reactivity with Human Adipocytes and Heart Fatty Acid Binding Proteins

Abstract: Cross-reactivity between allergens and human proteins could have a clinical impact in allergic diseases. Blo t 13 is an allergen from the mite Blomia tropicalis, which belongs to the fatty acid binding protein (FABP) family and has structural homology with human FABPs. This work aimed to map B cell epitopes on Blo t 13 and to identify epitopes involved in cross-reactivity with human heart FABP (FABP3) and adipocyte FABP (FABP4). Sera from 25 patients with house dust mite (HDM) allergy that were sensitized to B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Fatty acid binding. Cross-reactivity with Human Fatty acid binding protein and could induce an auto-reactive response [32].…”
Section: Bio T 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acid binding. Cross-reactivity with Human Fatty acid binding protein and could induce an auto-reactive response [32].…”
Section: Bio T 13mentioning
confidence: 99%
“…That is, IgE mediated self-reactivity, thus aggravating allergic reactions to a certain extent. Therefore, special attention should be paid to the possible cross-reactions between the dust mite allergens component 13 and the human body's own proteins in clinical diagnosis [32].…”
Section: Allergens Of Mite Component 13mentioning
confidence: 99%
“…The mAb 5G3 reacted with LvFABP, indicating that this allergen and Blo t 13 share an antigenic region, which can explain part of IgE reactivity as indicated by the inhibition assay using peptide five (Figure 3F). The mAb 5G3 binds to an epitope located in a region spanning residues 54 to 72 of Blo t 13 located in strands βD and βE, 23 and our sequence alignment revealed that this sequence is highly conserved between LvFABP and the FABP from HDM. ConSurf analysis supports that this region is involved in the cross‐reactivity between shrimp and B .…”
Section: Discussionmentioning
confidence: 82%
“…Epitope mapping was performed as indicated elsewhere 23,28 with modifications. One hundred µL of seven individual sera from shrimp allergic patients sensitized to LvFABP diluted 1:2, were preadsorbed with 150 µg/100 µL of each peptide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation